Techno-Economic Analysis of Co-firing for Pulverized Coal Boilers Power Plant in Indonesia - Zainal Arifin; Visang Fardha Sukma Insani; Muhammad Idris; Kartika Raras Hadiyati; Zakie Anugia; Dani Irianto (International Journal of Renewable Energy Development, 2023)
The utilization of co-firing (coal-biomass) in existing coal-fired power plants (CFPPs) is the fastest and most effective way to increase the renewable energy mix, which has been dominated by pulverized coal (PC) boilers, particularly in the Indonesian context. This study aims to investigate the technical and economic aspects of co-firing by conducting a pilot project of three PC boiler plants and capturing several preliminary figures before being implemented for the entire plants in Indonesia. Various measured variables, such as plant efficiency, furnace exit gas temperature (FEGT), fuel characteristic, generating cost (GC), and flue gas emissions, were identified and compared between coal-firing and 5%-biomass co-firing. The result from three different capacities of CFPP shows that co-firing impacts the efficiency of the plant corresponding to biomass heating value linearly and has an insignificant impact on FEGT. Regarding environmental impact, co-firing has a high potential to reduce SO2 and NOx emissions depending on the sulfur and nitrogen content of biomass. SO2 emission decreases by a maximum of 34% and a minimum of 1.88%. While according to economic evaluation, the average electricity GC increases by about 0.25 USD cent/kWh due to biomass price per unit of energy is higher than coal by 0.64×10-3 USD cent/kcal. The accumulation in the one-year operation of 5%-biomass co-firing with a 70% capacity factor produced 285,676 MWh of green energy, equal to 323,749 tCO2e and 143,474 USD of carbon credit. The biomass prices sensitivity analysis found that the fuel price per unit of energy between biomass and coal was the significant parameter to the GC changes.